Cleavage and Polyadenylation Specific Factor 1 Promotes Tumor Progression via Alternative Polyadenylation and Splicing in Hepatocellular Carcinoma - Chen, Shi-lu; Zhu, Zhong-xu; Yang, Xia; Liu, Li-li; He, Yang-fan; Yang, Ming-ming; Guan, Xin-yuan; Wang, Xin; Yun, Jing-ping (Frontiers in Cell and Developmental Biology, 2021)
Alternative polyadenylation (APA) is an important posttranscriptional regulatory mechanism required for 3’UTR mRNA cleavage and polyadenylation (CPA). It has been demonstrated that many aberrant APA events are present in hepatocellular carcinoma (HCC). However, the underlying regulatory mechanisms of APA remain unclear. In this study, we observed that cleavage and polyadenylation specific factor 1 (CPSF1), a major component of the CPA complex, increased significantly in HCC tissues and correlated with unfavorable survival outcomes. The knockdown of CPSF1 inhibited HCC cell proliferation and migration, whereas forced expression of CPSF1 exhibited the opposite effect. Based on integrative analysis of ISO-seq and RNA-seq data in HepG2.2.15 cells, we identified a series of transcripts with differential 3’UTR lengths upon the silencing of CPSF1 expression. This was related to the biological functions of gene transcription, cytoskeleton maintenance and endomembrane system transportation. Moreover, knockdown of CPSF1 induced a high number of alternative splicing (AS) events in addition to APA. Taken together, our study demonstrated that CPSF1 is a novel biomarker for HCC prognosis and a potential therapeutic target for treatment. This provided new insight into understanding HCC posttranscriptional regulation mechanisms.